2014
DOI: 10.1186/1471-2296-15-97
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes patients’ perspectives on lifestyle counselling and weight management in general practice: a qualitative study

Abstract: BackgroundLifestyle counselling is a pivotal aspect of diabetes care. But general practitioners (GPs) often have problems in finding their role in patients’ weight management. The aims of this study were to investigate the experiences of type 2 diabetes patients with lifestyle counselling from their GPs and to explore how patients’ preferences regarding counselling are embedded in the context of self-management and wider cultural aspects of nutrition.MethodsNarrative interviews were conducted with 35 people wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 23 publications
3
58
0
5
Order By: Relevance
“…37 Patients with chronic lower respiratory conditions also reported negative attitudes toward participating in selfmanagement programs where sessions last over 3 hours. 50 This finding was similar to what was found among patients living with cardiovascular disease 44 and type 2 diabetes, 53 who reported that self-management instructions are too complex and time consuming, making the recommendations too difficult to understand and integrate into their everyday lifestyles. Finally, patients living with chronic disease (ie, chronic lower respiratory conditions, diabetes, heart disease) in three studies reported negative attitudes toward group selfmanagement programs, because they did not know or were …”
Section: 49supporting
confidence: 64%
See 2 more Smart Citations
“…37 Patients with chronic lower respiratory conditions also reported negative attitudes toward participating in selfmanagement programs where sessions last over 3 hours. 50 This finding was similar to what was found among patients living with cardiovascular disease 44 and type 2 diabetes, 53 who reported that self-management instructions are too complex and time consuming, making the recommendations too difficult to understand and integrate into their everyday lifestyles. Finally, patients living with chronic disease (ie, chronic lower respiratory conditions, diabetes, heart disease) in three studies reported negative attitudes toward group selfmanagement programs, because they did not know or were …”
Section: 49supporting
confidence: 64%
“…37 Enrollment in self-management interventions was also negatively influenced by patients' limited knowledge about the pathophysiology of their disease, possible benefits of participating in self-management, and understanding the best self-management behaviors for improving symptom management. 37,44,[46][47][48][49][50][51][52][53] Additionally, patients were less likely to enroll and participate in self-management programs if the content and instructional methods were perceived as too complex or difficult to understand. Interestingly, patients living with cancer reported accessing patient education resources available both online and offline about their condition.…”
Section: Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…Такође је показано да када пацијенти почну да се придржавају дијете, после неког времена се осећају лоше и обично је преки-ну 13 . Wermeling 14 и остали аутори су дошли до резултата да пацијенти због одсуства бола и других знакова несхватају да су заиста бо-лесни и да морају правилније да се хране 14 . Од великог значаја је упућеност пацијента у своју болест, што често недостаје или се па-цијент информише из непоузданих извора.…”
Section: дискусијаunclassified
“…Several barriers have been identified for lifestyle behavior change. Some of these are: patients do not regard diabetes as a serious disease [31], misperception of the patients' actual lifestyle behavior [32], decrease in wellbeing [33], asymptomatic disease, increased costs, cultural background [11], patients are satisfied with their behavior [34], frustration from lack of success [35], physical limitations, lack of time [36] and interference with work [37]. In the end however, without being motivated, acquiring and maintaining a healthy lifestyle will probably be impossible.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%